The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.15835/nbha48111764
|View full text |Cite
|
Sign up to set email alerts
|

Controlled atmosphere and shelf life performance of a new late-maturing Japanese pear, Pyrus pyrifolia (Burm. F.) Nakai, cultivar ‘Atago’

Abstract: The aim of this research was to investigate the optimum storage condition, duration and shelf life performance of a new late-maturing Japanese pear cultivar ‘Atago’ under normal atmosphere, controlled atmosphere and shelf life conditions. For this purpose, fruits without injury or decay were divided into two groups. Group 1 (control) was stored in normal atmosphere; group 2 was stored in controlled atmosphere at 2.5% O2 + 1.5% CO2. The fruits were stored at 0 °C and 90-95% relative humidity for 32 weeks. 120 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…It can keep fruits and vegetables in a semi-dormant state, which helps to slow down the aging and deterioration process and achieve the purpose of preserving freshness and corrosion [ 48 ]. Previous results in fruits such as mangoes [ 49 ] and pears [ 50 ] showed that CA delayed the loss of fruit during the shelf life and attributed this to the positive effect of CA on fruit stabilization and maintenance of cellular integrity [ 51 ]. Similar results were found in our study, where CA significantly reduced the rate of decay of yellow peach during the shelf life.…”
Section: Discussionmentioning
confidence: 99%
“…It can keep fruits and vegetables in a semi-dormant state, which helps to slow down the aging and deterioration process and achieve the purpose of preserving freshness and corrosion [ 48 ]. Previous results in fruits such as mangoes [ 49 ] and pears [ 50 ] showed that CA delayed the loss of fruit during the shelf life and attributed this to the positive effect of CA on fruit stabilization and maintenance of cellular integrity [ 51 ]. Similar results were found in our study, where CA significantly reduced the rate of decay of yellow peach during the shelf life.…”
Section: Discussionmentioning
confidence: 99%
“…Weight loss and color measurement were performed in the same samples during storage. The weight loss (WL) (Dilmaçünal, 2020), peel color (Dilmaçünal, 2020), firmness (Ağar et al, 1997), titratable acidity (TA) and pH (Cemeroğlu, 2007), soluble solid content (SSC), decay amount, ascorbic acid (Vitamin C) content (Özdemir & Dündar, 1998), total phenolic substance amount (Coseteng & Lee, 1987), lycopene amount (Nagata & Yamashita, 1992), β-carotene amount and sensorial evaluations (calyx rupture and desiccation, external appearance, taste, and flavor) (Dilmaçünal, 2020) were performed during the cold storage and subsequent shelf-life period.…”
Section: Methodsmentioning
confidence: 99%